2022
DOI: 10.3390/jcm11195522
|View full text |Cite
|
Sign up to set email alerts
|

Fat Infiltration of Multifidus Muscle Is Correlated with Neck Disability in Patients with Non-Specific Chronic Neck Pain

Abstract: Chronic non-specific neck pain (CINP) is common, but the etiology remains unclear. This study aimed to examine the relationship between cervical muscle composition (cervical multifidus and longus capitis/longus colli), morphometry, range of movement, muscle function, and disability severity (Neck Disability Index) in patients with CINP. Methods: From September 2020 to July 2021, subjects underwent cervical MRI and clinical tests (cervical range of motion, cranio-cervical flexion test, neck flexor, and extensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Our results, suggesting an association between cervical muscle fat infiltration and clinical outcomes (e.g., mJOA score and Nurick scores), are in line with prior research in DCM and whiplash-associated disorders ( 11 , 12 ). Patients with whiplash-associated disorders who nominated self-recovery at 12-month post-injury had significantly less neck muscle fat infiltration in the multifidus muscle ( 33 ). The presence of greater fatty infiltration and asymmetry in these muscles may be associated with worse functional scores, clinical signs, and symptoms ( 8 , 14 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results, suggesting an association between cervical muscle fat infiltration and clinical outcomes (e.g., mJOA score and Nurick scores), are in line with prior research in DCM and whiplash-associated disorders ( 11 , 12 ). Patients with whiplash-associated disorders who nominated self-recovery at 12-month post-injury had significantly less neck muscle fat infiltration in the multifidus muscle ( 33 ). The presence of greater fatty infiltration and asymmetry in these muscles may be associated with worse functional scores, clinical signs, and symptoms ( 8 , 14 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with whiplash-associated disorders who nominated self-recovery at 12-month post-injury had significantly less neck muscle fat infiltration in the multifidus muscle ( 33 ). The presence of greater fatty infiltration and asymmetry in these muscles may be associated with worse functional scores, clinical signs, and symptoms ( 8 , 14 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirmed its clinical relevance in patients with neck pain as findings included muscle size (decreased cross-sectional area specifically at the affected side and level) and histology (increased intramuscular fatty infiltrates which correlates with pain-related disability) [3][4][5][6]. However, some of these findings are controversial and might depend on the neck pain etiology, duration, and severity [7].…”
Section: Introductionmentioning
confidence: 90%
“…The anatomy, function, and clinical relevance of the posterior deep neck muscles have been widely described in the literature [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. The cervical multifidus muscles are divided into superficial and deep fascicles, originating from the facet capsule of C4–C7 and inserted on the spinous process of C2 and the laminae of the superior vertebrae (just anterior to the base of the spinous process), respectively [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a clinical perspective, several studies have analyzed the correlation between the morphology and histology of the cervical multifidus and investigated differences between clinical populations and healthy or asymptomatic subjects [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. For instance, the intramuscular fatty infiltration percentage seems to be associated with cervical myelopathy (i.e., impaired sensorimotor function) [ 3 ], cervical spondylotic radiculopathy (i.e., poorer postural stability) [ 4 ], and non-specific chronic neck pain (i.e., greater disability) [ 5 ] severity. In addition to the intramuscular fatty infiltration, muscle morphology [ 6 , 7 , 8 ] and muscle function [ 9 , 10 , 11 ] are also relevant metrics to consider in several musculoskeletal conditions involving neck pain.…”
Section: Introductionmentioning
confidence: 99%